Augmented reality (AR) and virtual reality (VR) applications during Covid-19 pandemic among preclinical medical and dentistry students: a mini-review - Mohamad Zainal, Nurul Hayati; Ramli, Rosmaliza; Omar, Norsuhana; Mahmud, Melati; Abdul Salim, Noor Hafizah (UPM Press, 2022)
The efficacy of online learning in delivering theoretical knowledge with appropriate content to students is imperative, especially in the Covid-19 pandemic era. Substantial interactive teaching materials were developed for higher education. However, some were designed immensely general, especially in fulfilling the syllabus of preclinical medical and dentistry students. Augmented reality (AR) is an interactive three-dimension (3D) experience that uses computers to overlay virtual information in the real world whereas virtual reality (VR) is a computer-generated artificial recreation of a real-life experience or situation. Interestingly, both can be complemented and integrated into online and traditional teaching methods. Implementation of these technologies will increase the learning efficacy in understanding the human body’s anatomical and physiological changes in the normal or pathological state. As AR and VR technologies are continuously evolving, this review provides the preview and current updates on AR and VR applications in medical and dentistry education which may benefit the educators within these specialities.